A comprehensive psychometric evaluation of the UK FIM + FAM. (October 2013) - Turner-Stokes, Lynne; Siegert, Richard J.
Abstract Purpose: To evaluate the psychometric properties of the UK FIM + FAM. Methods: (a) A systematic literature review integrating the evidence for psychometric qualities of both the original and UK versions, and (b) exploratory and confirmatory factor analysis of admission/discharge data from an inpatient general neuro-rehabilitation cohort using parametric and non-parametric techniques. A prospective cohort of 459 patients with a male:female ratio of 57:43 and mean age of 44.5 (SD 14.3) years participated in this study. Results: Seven published articles together demonstrated acceptable utility, concurrent validity, inter-rater reliability and responsiveness of the UK FIM + FAM. Factor analysis demonstrated that all items loaded high (>0.58) on the first principal component and distinct motor and cognitive factors emerged after rotation. A four-factor solution also demonstrated four distinct, interpretable dimensions (Physical, Psychosocial, Communication and Extended Activities of Everyday Living (EADL)). Mokken analysis of the second data set confirmed these dimensions. Cronbach's αs were 0.97 and 0.96 for the motor and cognitive domains and 0.90–0.97 for the subscales. Analysis of responsiveness demonstrated "large" effect sizes (0.86–1.29). Conclusions: The UK FIM + FAM, including the newer EADL module, is a valid, reliable scale of functional independence. It has high internal consistency in two domains and four subscales and is responsive to changes occurring in a general inpatient neuro-rehabilitation population. Implications for Rehabilitation The UK FIM + FAM is a valid, reliable scale of functional independence, which is responsive to changes occurring in a general inpatient neuro-rehabilitation population. It can be used to derive a reliable, single score of overall independence and also yields specific information in two main domains and four separate subscales of independence: Physical, Psychosocial, Communication and Extended Activities of Daily Living (EADL). The newer EADL item module provides added value, measuring functional independence for community-based activities.